Quantitative multimodal assessment of concussion recovery in youth athletes - Howell, D. R.; Myer, G. D.; Brilliant, A.; Barber Foss, K.; Meehan, W. P. (Clinical Journal of Sport Medicine, 2021)
Objective: To evaluate recovery trajectories among youth athletes with a concussion and healthy controls across different domains using a quantitative and multifaceted protocol. Study Design: Prospective repeated measures. Participants: Youth athletes diagnosed with a concussion between the ages of 8 and 18 years were evaluated (1) within 10 days after injury, (2) approximately 3 weeks after injury, and (3) after return-to-play clearance. Control participants completed the same protocol. Setting: Sport concussion clinic. Interventions: N/A. Main Outcome Measures: Participants underwent a multifaceted protocol that assessed symptoms (postconcussion symptom scale [PCSS]), dual-task gait, event-related potentials (ERPs), and eye tracking. Results: Sixty-seven athletes participated: 36 after concussion (age = 14.0 ± 2.6 years; 44% female) and 31 controls (age = 14.6 ± 2.2 years; 39% female). Concussion symptoms were higher for the concussion group compared with controls at the first (PCSS = 31.7 ± 18.8 vs 1.9 ± 2.9; P < 0.001) and second time points (PCSS = 10.8 ± 11.2 vs 1.8 ± 3.6; P = 0.001) but resolved by the final assessment (PCSS = 1.7 ± 3.6 vs 2.0 ± 3.8; P = 0.46). The concussion group walked slower during dual-task gait than controls at all 3 tests including after return-to-play clearance (0.83 ± 0.19 vs 0.95 ± 0.15 m/s; P = 0.049). There were no between-group differences for ERP connectivity or eye tracking. Those with concussions had a decrease in ERP connectivity recovery over the 3 time points, whereas control participants' scores increased (concussion d = -8.7 ± 28.0; control d = 13.9 ± 32.2; X² = 14.1, P = 0.001). Conclusions: Concussion is associated with altered dual-task gait speeds after resolution of concussion symptoms, but ERP and eye tracking measures did not demonstrate between-group differences across time. Some objective approaches to concussion monitoring may support with identifying deficits after concussion, but further work is required to delineate the role of gait, electrophysiological, and eye tracking methods for clinical decision-making.